Perspectives and Challenges of Assessment in ELT in Higher Education: A Review Paper - Khatri, Chitra Bahadur (Journal of Educational Research and Innovation, 2024)
This review paper examines the challenges associated with assessing English language teaching (ELT) in higher education, encompassing natural obstacles and issues stemming from assessment systems. It evaluates traditional and modern assessment methods, including summative, formative, developmental, and elective exams, while examining their strengths and limitations. The paper also explores the impact of technological advances on assessment practices and emphasizes critical factors such as socioeconomic disparities, linguistic diversity, and the alignment of assessments with learning outcomes. Through a review of literature and case studies, the paper illuminates the influence of assessments on teaching and learning, considering perspectives from both teachers and students, test anxiety, and educational diversity. Key findings underscore the potential of technology to enhance assessment flexibility, yet persistent socioeconomic and linguistic barriers hinder equitable evaluation. The article advocates for adopting more adaptive and inclusive strategies, emphasizing the importance of a balanced approach that fosters fair, effective, and comprehensive ELT assessments in higher education.